Three Poems - Wolfe, Kathi (Disability Studies Quarterly, 2008)
Kathi Wolfe is a poet and writer. She was a finalist in the 2007 Pudding House Press Chapbook Competition. Her chapbook Helen Takes the Stage: The Helen Keller Poems was published in 2008 by Pudding House Press. Wolfe's poetry has appeared in Wordgathering, Breath & Shadow, Gargoyle, Potomac Review, Beltway Poetry Quarterly and other publications. She has read at the Library of Congress Poetry at Noon Series and appeared on the public radio show "The Poet and the Poem."